(untitled) (Polish Yearbook of International Law, 2021)
With the Act on the Polish Card Poland followed the pattern of some European states (mostly Central and Eastern European ones) of enacting specific domestic legislation conferring special treatment and benefits to persons who are recognized as its kin-minorities. The most important analysis of this phenomenon from the perspective of international law was the 2001 Venice Commission’s report entitled “Report on the Protection of National Minorities by their Kin-State.” The Polish legislation was adopted in 2007, so for obvious reasons it was not considered by the Venice Commission. However, a rather unexpected and unusual examination of the Polish kin-state legislation from the perspective of international law came from Belarus. The Constitutional Court of the Republic of Belarus (CCRB) conducted a comprehensive examination of the Act on the Polish Card in 2011. The main aim of this article is to present and comment on the reasoning of the CCRB. Beginning with the broader context, this article starts with a presentation of the origins and a short description of the Act on the Polish Card, followed by a discussion of why the Polish Card and other kin-state legislation instruments are topics of concern in international law. The main part of the article is devoted to the presentation and assessment of the 2011 CCRB decision on the Act on the Polish Card. The author’s assessment confirms at least some of the concerns put forward by the CCRB, i.e., that both the Act on the Polish Card and the practice based on it contradict some norms and principles of international law, namely the principle of territorial sovereignty, the norms of consular law, and several bilateral treaties in force between these two states. Bearing in mind that despite those concerns more than a quarter-million Polish Cards (also sometimes called Pole’s Cards) have been issued so far by the Polish authorities, the article ends with a discussion of why such a prolonged nonconformity with international law is possible.